PREDIKTOR DETERMINAN BERAT BADAN LAHIR BAYI DI WILAYAH KERJA PUSKESMAS LINGKAR TIMUR KOTA BENGKULU TAHUN 2011 - Witradharma, Tetes Wahyu (JURNAL MEDIA KESEHATAN, 2012)
Nutrition for pregnant women is very influential on the fetus. Poor maternal nutritional status before conception and during pregnancy will lead to low birth weight infants (LBW), fetal brain growth retardation, anemia on fetus, susceptible to infectious diseases and abortion. The aim is to determine determinant predictor of infant birth weight in Puskesmas Lingkar Timur Area Bengkulu City 2011. This study used cross sectional by analytic approach. The sample were 88 people. Data obtained in Puskesmas Lingkar Timur Area Bengkulu City from January to February 2011. Data research used secondary data which consisted of weight gain of pregnant women TM2, TM3, MUAC, Hb, iron (Fe), infant birth weight that obtained from the register book KIA BPS in Puskesmas Lingkar Timur Area Bengkulu City. Significant value of MUAC 0.0005 (p <0.05) and significant value of Hb 0.0005 (p <0.05). This study shows that MUAC and Hb are determinant predictor of weight infants. Therefore it is necessary for the promotion of research results that can be followed by monitoring nutrient intake and nutritional status in pregnant women.